Top 3 differentials in radiology a case review - O'Brien, William T., Sr (Thieme, 2018)
Praise for the first edition: ""Innovative...it would be difficult to find a better high-yield, high-quality textbook covering every subsection of the radiology...board examination."" - JAMA ""Extremely useful for practicing radiologists and radiology residents looking to...acquire the most pertinent knowledge in preparation for board exams, recertification, and general practice...This high-yield way of learning allows the rapid development of...differential diagnoses...for the full range of entities commonly encountered in practice and board exam settings."" - Academic Radiology ""One of the.